Ethical dilemmas in marketing: A rationale - Hensel, Paul J. (Journal of business ethics, 1986)
Because of their visibility, marketers are often perceived by society as engaging in unethical or questionable behaviors. The marketing literature does not specifically provide an explanation for this dilemma. This paper suggests that there are three major reasons for this problem: fluctuating limits of consensus, ethnocentrism, and utilitarian economic analyses.